2021
DOI: 10.1002/er.7046
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of hydrogen storage characteristics of catalyst free magnesium nanoparticles prepared by wet milling

Abstract: Magnesium is one of the potential candidates for on-board hydrogen storage, but slow hydrogenation kinetics and unfavourable thermodynamics limits its practical implementation. To improve the hydrogenation characteristics, nanocrystalline magnesium was prepared by a simple wet milling method without addition of heavy metal catalyst. Compared to micro-crystalline Mg, developed nanocrystalline Mg exhibits improved hydrogen storage properties showing extended plateau region in the pressure-composition-temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 65 publications
(68 reference statements)
0
7
0
Order By: Relevance
“…Nevertheless, if Mg is properly prepared and incorporated with catalysts, these drawbacks can be overcome. He et al showed that for 2.25% V decorated Mg nanoblade array, [ 118,119 ] the hydrogen absorption activation energy can be reduced to 35 kJ mol −1 H 2 (compared to 65–81 kJ mol −1 H 2 for Mg powder) [ 120 ] and desorption activation energy to 65 kJ mol −1 H 2 (compared to 120–156 kJ mol −1 H 2 for MgH 2 powder). [ 121 ] In addition, the current review shows that Pd binary or ternary alloys can also be used to significantly improve the performance of PHS, but systematic studies on the fabrication and optical properties of these or other alloys are rare.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, if Mg is properly prepared and incorporated with catalysts, these drawbacks can be overcome. He et al showed that for 2.25% V decorated Mg nanoblade array, [ 118,119 ] the hydrogen absorption activation energy can be reduced to 35 kJ mol −1 H 2 (compared to 65–81 kJ mol −1 H 2 for Mg powder) [ 120 ] and desorption activation energy to 65 kJ mol −1 H 2 (compared to 120–156 kJ mol −1 H 2 for MgH 2 powder). [ 121 ] In addition, the current review shows that Pd binary or ternary alloys can also be used to significantly improve the performance of PHS, but systematic studies on the fabrication and optical properties of these or other alloys are rare.…”
Section: Discussionmentioning
confidence: 99%
“…Milled MPF-4 magnesium powder of high purity (99.2%) with a particle size of 50–300 µm was used as the investigated material [ 22 , 23 , 24 , 25 ]. Magnesium hydride powder and dehydrogenated MgH 2 powder were also used for testing.…”
Section: Methodsmentioning
confidence: 99%
“…In this respect, diverse strategies for tackling such hostile thermodynamic and kinetic properties of unmodified hydride materials have been explored, including nanosizing hydrides and incorporating additive species. In particular, it has been widely shown that the nanosizing of hydride materials can induce distinct changes in thermodynamic , and kinetic properties, improving the hydrogen storage performance compared to those of the bulk counterparts for both metal hydrides and complex hydrides …”
Section: Introductionmentioning
confidence: 99%